Usability Test of Mental Health Application MoodPath with Software Usability Measurement Inventory - Utomo, Victor Gayuh; Widhiastuti, Hardani; Heryanti, Rini; Susilo, Markus Nanang I. B. (Jurnal Transformatika, 2025)
MoodPath is a mobile application for mental health. The application uses Patient Health Questionnaire 9 (PHQ-9) and General Anxiety Disorder 7 (GAD-7) to assess mental health of its users. The study held usability test using Software Usability Measurement Inventory (SUMI) questionnaire with 27 respondents. MoodPath application got usability value of 46.26 that is Below Average in Global SUMI scales. The value is also related with every individual scale in SUMI. The Efficient, Affect, Helpfulness and Control scales have Below Average value. Only the Learnability scale has Above Average value. The usability result is reached with 95% Confidence Interval. Based on the IT skill, respondents with better IT skill gave lower usability score compared to respondent with lesser IT skill. The research also found that familiar UI and standard questionnaire (PHQ-9 and GAD-7) gave positive usability in Learnability and Efficiency scale. The research found that MoodPath application need to consider wider range of users by giving feature that not only satisfied people with lesser IT skill but also people with better IT skill. Based on the usability test, the MoodPath application may improve the usability by providing ‘Remember Me’ and result saving features.